2016
DOI: 10.1080/01441647.2016.1245219
|View full text |Cite
|
Sign up to set email alerts
|

Tradable credits for managing car travel: a review of empirical research and relevant behavioural approaches

Abstract: Recently, there has been a surge of interest in Tradable Credits (TC) as an alternative measure to manage the growth of personal car use. This paper summarises the results and methodologies of studies that have sought to anticipate the behavioural responses to several proposed TC schemes that target personal travel. In a critical reflection on this work and in an attempt to inspire future research, we argue that future empirical studies on TC behaviours can greatly benefit from insights from the fields of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 105 publications
0
38
0
Order By: Relevance
“…This finding might be explained by a cost hierarchy present in change options, implying that generally people first select alternatives that are less costly in terms of money and effort, and that additional change is more costly and therefore more difficult to achieve (Loukopoulos et al, 2006). It might also indicate a 'shock effect' in scenario 1, that is, the introduction of the measure has an effect apart from the total credits available (Dogterom et al, 2017). Of course, fatigue could also have played a role, as people might have been less motivated to take scenario 2 seriously because of the complexity and time required for the experiment.…”
Section: Data Collection Processmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding might be explained by a cost hierarchy present in change options, implying that generally people first select alternatives that are less costly in terms of money and effort, and that additional change is more costly and therefore more difficult to achieve (Loukopoulos et al, 2006). It might also indicate a 'shock effect' in scenario 1, that is, the introduction of the measure has an effect apart from the total credits available (Dogterom et al, 2017). Of course, fatigue could also have played a role, as people might have been less motivated to take scenario 2 seriously because of the complexity and time required for the experiment.…”
Section: Data Collection Processmentioning
confidence: 98%
“…For a detailed discussion of this literature, we refer to Dogterom et al (2017); here, we summarise the most important findings and methodological aspects. Empirical research started by exploring public opinion and general intentions.…”
Section: Literaturementioning
confidence: 99%
“…These policies have generally a n egative impact on citizens, while, as reported in EPOMM [5] and Dogteron et al [6], rewards are well accepted. In Tillema et al [7] rewarding and penality systems are compared; moreover these authors show that a theoretical pricing solution should make each user pay the cost that the society has to bear because of his mobility habits.…”
Section: Mobility Rewarding Strategies and Softwares: The State Of Artmentioning
confidence: 99%
“…Besides the recently surge of interest with theoretical approaches of TCS, its empirical studies provides insights to implement the TCS in the future, as concluded in Dogterom, Ettema and Dijst (2017), which has emphasized the importance of understanding the impact of TCS on personal car travel.…”
Section:  Implementation Of the Tcsmentioning
confidence: 99%
“…However, the tradable credits scheme appears to be a promising policy tool for mobility management and has received increasing attention in recent years, as demonstrated in some recent review papers, i.e. Fan and Jiang (2013), Grant-Muller and Xu (2014) and Dogterom, Ettema and Dijst (2017), where Fan and Jiang (2013) provided a comparative summary of different TCSs, Grant-Muller and Xu (2014) investigated to what extent in existing literature suggest TCS could be feasibly implemented with the target of road traffic congestion management, and Dogterom, Ettema and Dijst (2016) presented a review on the empirical studies on TCS and behavioural concepts and theories from the fields of behavioural economics and cognitive psychology that they considered these are relevant to account for decision-making with TCS and impact of TCS on personal car travel.…”
Section: Introductionmentioning
confidence: 99%